(x-2/x+2)^2+3-4(x-2/x+2)=6
solve by splitting the middle term
Answers
Answered by
1
Answer:
hiiii mate ☺️
your solution is attached with this picture....
hope it helps you ✌️✌️
Attachments:
![](https://hi-static.z-dn.net/files/dc1/908c50c5988701d4d7b1d775d27d7fa3.jpg)
Answered by
6
Step-by-step explanation:
Let's solve your equation step-by-step.
4x+2=2(x+6)
Step 1: Simplify both sides of the equation.
4x+2=2(x+6)
Simplify:
4x+2=2x+12
Step 2: Subtract 2x from both sides.
4x+2−2x=2x+12−2x
2x+2=12
Step 3: Subtract 2 from both sides.
2x+2−2=12−2
2x=10
Step 4: Divide both sides by 2.
2x/2=10/2
x=5 Answer
Similar questions
Science,
6 months ago
Social Sciences,
6 months ago
Math,
1 year ago
Social Sciences,
1 year ago
Hindi,
1 year ago